Early Changes in B and Plasma Cell Subsets and Traditional Serological Markers as Predictors of SRI-4 Response to Therapy in Systemic Lupus Erythematosus - Parodis, Ioannis; Gomez, Alvaro; Lindblom, Julius; Chow, Jun Weng; Doria, Andrea; Gatto, Mariele (Frontiers in Medicine, 2022)
Objective With the premise of the hypothesis that early biological responses to therapy for active systemic lupus erythematosus (SLE) portend later clinical improvements, we studied changes in B cell subsets and traditional serological markers in relation to clinical response to standard therapy (ST) with or without the addition of belimumab. Patients and Methods We analyzed data from the BLISS-76, BLISS-SC, and BLISS Northeast Asia trials (N = 1712). Circulating CD19+ B cell subsets were determined by flow-cytometry. We studied associations of relative to baseline percentage changes in circulating B and plasma cell subsets, anti-dsDNA antibody levels and complement levels with SLE Responder Index (SRI)-4 response after 52 weeks of treatment. Changes occurring through week 8 were deemed “rapid,” through week 24 “early,” and thereafter “delayed”. Results In the analysis of the entire cohort, SRI-4 responders showed more prominent decreases from baseline through week 52 in CD19+CD20+CD27– naïve B cells (median change: −61.2% versus −50.0%; P = 0.004), CD19+CD20–CD27bright plasmablasts (−44.9% versus −33.3%; P = 0.011), and CD19+CD20–CD138+ long-lived plasma cells (−48.2% versus −37.1%; P = 0.024), and a more prominent rapid (+92.0% versus +66.7%; P = 0.002) and early (+60.0% versus +49.5%; P = 0.033) expansion of CD19+CD20+CD27+ memory B cells than non-responders. More prominent rapid reductions in anti-dsDNA (−14.8% versus −8.7%; P = 0.043) and increases in C3 (+4.9% versus +2.1%; P = 0.014) and C4 levels (+11.5% versus +8.3%; P = 0.017) were documented in SRI-4 responders compared with non-responders among patients who received add-on belimumab, but not among patients who received non-biological ST alone. Conclusion SRI-4 responders showed a more prominent rapid expansion of memory B cells and more prominent delayed reductions in naïve B cells, plasmablasts and long-lived plasma cells. Moreover, clinical response to belimumab was associated with preceding more prominent reductions of anti-dsDNA and increases in C3 and C4 levels. Monitoring biological changes may prove useful in SLE patient surveillance and early treatment evaluation.